Sweet, nutritious, and diverse fruits: the genetic heritage of Butia odorata palm groves in southern Brazil - Lima, Carlos Fellipe Meurer de; Wagner, Julia Goetten; Vahl, Bianca Rodeghiero; Ferri, Nubia Marilin Lettnin; Sosinski Júnior, Ênio Egon; Mistura, Claudete Clarice; Vizzotto, Márcia; Barbieri, Rosa Lía (Food Science and Technology, 2025)
The Butia genus comprises 22 palm species native to South America. These palms produce fruits popularly known as butiás, which have high levels of minerals, vitamin C, and carotenoids. These plants are underutilized and threatened with extinction due to human activities. Considering the need to promote local foods beneficial to health and develop conservation strategies for endangered species, it is essential to characterize the genetic resources of Butia spp. This study aimed to evaluate biometric, physicochemical, colorimetric characteristics, proximate composition, and bioactive compounds in fruits of Butia odorata (Barb.Rodr.) Noblick in southern Brazil. Mature fruits from 10 palms were collected in two in situ conservation areas. All analyses were performed in triplicate, and the data were subjected to analysis of variance and the Scott-Knott test (p ≤ 0.05) for mean comparison using the RStudio statistical software. The analyses revealed significant statistical differences among the palms for the evaluated variables. Compared to other studies on the same species, the results show that the evaluated palms produce fruits rich in ascorbic acid, with high total soluble solids (TSS), high antioxidant activity, and carotenoid concentration, as well as lower fat content and reduced acidity. The genotypes also exhibited variability in colorimetric parameters, with a yellowish hue in the fruits. Higher consumer acceptance of fruits is associated with higher TSS content, which is related to the sugar content in the pulp, and lower acidity. The results demonstrate the high functional potential of these fruits and highlight genetic variability among the evaluated individuals regarding biometric, physicochemical, proximate composition, bioactive compounds, and colorimetric attributes. The results confirm the species’ potential to contribute to both dietary health and biodiversity conservation. These findings support future efforts to value sustainable gathering through the promotion of functional food products while protecting remnant palm landscapes through integrated socioecological strategies.